Development of Web-Based Scholarship Portal Using Matching Jaro-Winkler Algorithms - Kressa, Audhy Virabri; Sudarmaningtyas, Pantjawati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
Scholarships are benefits that aim to help with learning costs. Scholarship information is still spread on each web, making it difficult to search. This study aims to build a web portal that focuses scholarship information. The web portal built automatically collects periodic scholarship data using Curl. The source of information used comes from existing portals and scholarship provider web agencies. After the data is obtained the system will match with the Jaro-Winkler method to avoid duplication of stored data. Based on the results of unit testing on the function results obtained 98.91%. Based on the results of trials on system functions, the results of 99% were obtained in one and two iterations. These results indicate that this study has succeeded in implementing up-to-date centralization of information with the matching algorithm Jaro-Winkler. The Final Project focuses on the functionality of the Scholarship Portal, so that the User Interface (UI) and User Experience (UX) of the scholarship portal are not prioritized. Further research can be improved by User Interface (UI) and User Experience (UX) so that users can use the application easily.